Search for a signature of Pauli exclusion principle violation by VIP-2. (1st August 2022) - De Paolis, L; Napolitano, F; Bartalucci, S; Bazzi, M; Bertolucci, S; Bragadireanu, M; Capoccia, C; Cargnelli, M; Clozza, A; Del Grande, R; Fiorini, C; Guaraldo, C; et al.
Abstract: The VIP-2 experiment performs a high sensitivity test of the Pauli Exclusion Principle for electrons, and is operated in the ultra-low cosmic background environment of the Gran Sasso Underground Laboratories of INFN. The experimental technique consists in testing the symmetry state of an open, continuously supplied, system of fermions; thus representing the only spin-statistics test which strictly fulfills the Messiah-Greenberg superselection rule. In April 2019, VIP-2 started the ongoing data taking campaign in its final layout, with the goal to improve the previous VIP result of at least two orders of magnitude. Before April 2019, VIP-2 collected, in a partial configuration of the external shielding complex, two sets of data in 2018–2019 for a total duration of about 208 days. We present in this work the results of the analyses of the first two data sets collected by VIP-2, which already improve the VIP result by one order of magnitude. The results are also interpreted in the framework of a diffusion random walk model, which provides a significantly enhanced description of the electrons-atoms close encounters process, and hence a boost on the estimated limit on the Pauli Exclusion Principle violation probability.